Deformation driven Seq2Seq longitudinal tumor and organs‐at‐risk prediction for radiotherapy. Issue 9 (3rd August 2021) - Lee, Donghoon; Alam, Sadegh R.; Jiang, Jue; Zhang, Pengpeng; Nadeem, Saad; Hu, Yu‐chi
Abstract: Purpose: Radiotherapy presents unique challenges and clinical requirements for longitudinal tumor and organ‐at‐risk (OAR) prediction during treatment. The challenges include tumor inflammation/edema and radiation‐induced changes in organ geometry, whereas the clinical requirements demand flexibility in input/output sequence timepoints to update the predictions on rolling basis and the grounding of all predictions in relationship to the pre‐treatment imaging information for response and toxicity assessment in adaptive radiotherapy. Methods: To deal with the aforementioned challenges and to comply with the clinical requirements, we present a novel 3D sequence‐to‐sequence model based on Convolution Long Short‐Term Memory (ConvLSTM) that makes use of series of deformation vector fields (DVFs) between individual timepoints and reference pre‐treatment/planning CTs to predict future anatomical deformations and changes in gross tumor volume as well as critical OARs. High‐quality DVF training data are created by employing hyper‐parameter optimization on the subset of the training data with DICE coefficient and mutual information metric. We validated our model on two radiotherapy datasets: a publicly available head‐and‐neck dataset (28 patients with manually contoured pre‐, mid‐, and post‐treatment CTs), and an internal non‐small cell lung cancer dataset (63 patients with manually contoured planning CT and 6 weekly CBCTs). Results: The use of DVF representation and skip connections overcomes the blurring issue of ConvLSTM prediction with the traditional image representation. The mean and standard deviation of DICE for predictions of lung GTV at weeks 4, 5, and 6 were 0.83 ± 0.09, 0.82 ± 0.08, and 0.81 ± 0.10, respectively, and for post‐treatment ipsilateral and contralateral parotids, were 0.81 ± 0.06 and 0.85 ± 0.02. Conclusion: We presented a novel DVF‐based Seq2Seq model for medical images, leveraging the complete 3D imaging information of a relatively large longitudinal clinical dataset, to carry out longitudinal GTV/OAR predictions for anatomical changes in HN and lung radiotherapy patients, which has potential to improve RT outcomes.